Remote Work Satisfaction of University Academics. Case Study of Poland: Part 2 – Research Results - Marta MOCZULSKA; Renata WINKLER (Communications of International Proceedings, 2021)
The aim of the study was to identify factors important from the point of view of remote work satisfaction of academic staff. The study involved a group of sixteen full-time research and teaching staff from state universities, who due to solutions introduced in their workplaces to limit SARS-CoV-2 virus transmission were obligated to perform their work remotely. University academics were take part in the study after having already worked remotely for two semesters. Considering the importance of individual factors for both job satisfaction and remote working, only individuals with academic degrees (assistant professor and professor) employed as professors and assistant professors were recruited with equal proportions of: (1) women and men, (2) those representing technical and non-technical disciplines (qualification criterion adopted: engineering degree), (3) those with minor children in care and those with no minor children in the household. The study was conducted using the method of semi-structured in-depth interview. Due to editorial limitations related to the acceptable volume of the text, the text of publication was divided into two parts. The first part of the study includes: introduction, Literature review, methodology and description of research process. The second part of the study contains research results, conclusions, indications of limitations of the results and suggestions developed in the context of the obtained results.
Keywords: Job Satisfaction; Remote Work; University Academics